2017
DOI: 10.2174/1574892812666170424150407
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Mesenchymal Transition in Cancer Progression: Prev entive Phytochemicals

Abstract: EMT is a significant pharmacological target for developing preventive agents to combat pathological conditions like malignancy. Many of the phytochemicals cited in this review are being enrolled for different phases of clinical trials for their efficacy. In spite of the major limitations regarding bioavailability, sensitivity and tolerance of these compounds, their synthetic analogs, formulations and efficient drug delivery systems are also being attempted which will hopefully generate productive and promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…It is generally agreed that simple polyphenolics are readily absorbed by the intestinal tract . Moreover, in most studies, microgram quantities of individual polyphenols have been shown to exert varied biological effects . It is thus possible that the reversal of hepatosteatosis in VCO‐treated rats could be partially due to its polyphenol content.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that simple polyphenolics are readily absorbed by the intestinal tract . Moreover, in most studies, microgram quantities of individual polyphenols have been shown to exert varied biological effects . It is thus possible that the reversal of hepatosteatosis in VCO‐treated rats could be partially due to its polyphenol content.…”
Section: Discussionmentioning
confidence: 99%
“…GA inhibits the expression of invasion-and EMT-related molecules in HepG2 cells. Epithelial-mesenchymal transition (EMT), which endows tumor cells with enhanced motility and invasion capacities, is a prerequisite for tumor infiltration and metastasis (21). In order to investigate the effect of GA on the expression of invasion-related genes (MMP-2 and MMP-9) and EMT-related genes (E-cadherin, ZO-1, vimentin and N-cadherin), HepG2 cells were treated with GA (25 and 50 µM) for 24 h and then the total cell RNA was extracted and subjected to RT-qPCR analysis.…”
Section: Ga Suppresses the Proliferation Migration And Invasion Abilmentioning
confidence: 99%
“…3D). In addition, epithelial-mesenchymal transformation (EMT) plays an important role in the occurrence, development and metastasis of tumors [28,29]. Key transcription factors, including E-cadherin, Ncadherin and vimentin, are extensively involved in the regulation of the EMT process [30].…”
Section: Liquiritin Inhibits Migration and Invasion Of Colorectal Canmentioning
confidence: 99%